Doublet Chemotherapy in the Elderly Patient With Ovarian Cancer - Teo, Min Y.; Power, Derek G.; Tew, William P.; Lichtman, Stuart M. (The oncologist (Dayton, Ohio), 2012)
Learning Objectives After completing this course, the reader will be able to: Summarize trends in the treatment of older women with ovarian cancer. Describe the potential value of performing a geriatric assessment prior to treatment in older women with ovarian cancer. This article is available for continuing medical education credit at CME.TheOncologist.com The aging of the population has focused on the need to evaluate older patients with cancer. Approximately 50% of patients with ovarian cancer will be older than age 65 years. Increasing age has been associated with decreased survival. It is uncertain whether this relates to biologic factors, treatment factors, or both. There is concern that undertreatment may be associated with decreased survival. Older patients with ovarian cancer have been underrepresented in clinical trials. Therefore, the evidence base on which make decisions is lacking. Clinicians need to be aware of the currently available data to aid in treatment decisions. Doublet therapy is the most common standard treatment in epithelial ovarian cancer. It usually consists of a taxane and a platinum compound. A series of cooperative group studies in both the United States and Europe established intravenous paclitaxel and carboplatin as the most common standard in optimally debulked patients. The recent introduction of intraperitoneal therapy has complicated decision making in terms of which older patients would benefit from this more toxic therapy. In relapsed patients, the issue of platinum sensitivity is critical in deciding whether to reutilize platinum compounds. It is unclear whether single agents or combinations are superior, particularly in older patients. Geriatric assessment is an important component of decision making. Prospective studies are needed to develop strategies to determine the optimal treatment for older patients with ovarian cancer. 摘要 当前人口老龄化问题使得人们开始关注对老年癌症患者进行评估的需求。约50%的卵巢癌患者超过65岁。年龄增长与生存率降低相关。尚未确定这一现象是否与生物学因素、治疗因素相关，或与二者均相关。目前存在的忧虑的是治疗不足可能与生存率降低有关。在临床试验中历来很少纳入老年卵巢癌患者。因而治疗决策的证据欠充足。临床医生需要了解现有数据以助制定治疗决策。双药联合方案是上皮性卵巢癌最常用的标准治疗。该方案通常由一种紫杉烷类药物与一种铂类化合物组成。由美国和欧洲共同完成的一系列协作组研究显示，静脉紫杉醇和卡铂是理想肿瘤细胞减灭术患者最常用的标准治疗。近期引入的腹腔内治疗为治疗决策提供了更多选择，就这一点而言，老年患者可能从这种毒性更高的治疗中获益。对于复发患者，铂类敏感性问题对于是否再次使用铂类化合物的决策至关重要。目前尚未明确单药或联合治疗孰优孰劣，特别是对于老年患者。老年人身心健康评价是治疗决策制定中的重要组成部分。今后尚需开展前瞻性研究，以制定老年卵巢癌患者的最佳治疗策略。 This study examines treatment options for older patients with ovarian cancer. Older patients with ovarian cancer have been underrepresented in clinical trials, so the evidence base on which physicians make decisions is lacking. Clinicians need to be aware of the currently available data to aid in treatment decisions.